Resveratrol induces cell death and inhibits human herpesvirus 8 replication in primary effusion lymphoma cells. (5th December 2015) - Tang, Feng-Yi; Chen, Chang-Yu; Shyu, Huey-Wen; Hong, Shin; Chen, Hung-Ming; Chiou, Yee-Hsuan; Lin, Kuan-Hua; Chou, Miao-Chen; Wang, Lin-Yu; Wang, Yi-Fen
Abstract: Resveratrol (3, 4′, 5-trihydroxy-trans-stilbene) has been reported to inhibit proliferation of various cancer cells. However, the effects of resveratrol on the human herpesvirus 8 (HHV8) harboring primary effusion lymphoma (PEL) cells remains unclear. The anti-proliferation effects and possible mechanisms of resveratrol in the HHV8 harboring PEL cells were examined in this study. Results showed that resveratrol induced caspase-3 activation and the formation of acidic vacuoles in the HHV8 harboring PEL cells, indicating resveratrol treatment could cause apoptosis and autophagy in PEL cells. In addition, resveratrol treatment increased ROS generation but did not lead to HHV8 reactivation. ROS scavenger (N-acetyl cysteine, NAC) could attenuate both the resveratrol induced caspase-3 activity and the formation of acidic vacuoles, but failed to attenuate resveratrol induced PEL cell death. Caspase inhibitor, autophagy inhibitors and necroptosis inhibitor could not block resveratrol induced PEL cell death. Moreover, resveratrol disrupted HHV8 latent infection, inhibited HHV8 lytic gene expression and decreased virus progeny production. Overexpression of HHV8-encoded viral FLICE inhibitory protein (vFLIP) could partially block resveratrol induced cell death in PEL cells. These data suggest that resveratrol-induced cell death in PEL cells may be mediated by disruption of HHV8 replication. Resveratrol may be a potential anti-HHV8 drug and an effective treatment for HHV8-related tumors. Graphical abstract: Highlights: Resveratrol induced apoptosis, autophagy and ROS generation in HHV8 harboring PEL cells. Resveratrol induced ROS generation did not lead to HHV8 reactivation but inhibited HHV8 virus progeny production. Resveratrol inhibited HHV8 gene expression and replication leading to PEL cell death. Resveratrol can be an anti-HHV8 drug and a potential therapy for HHV8-related tumors.